NILAI-NILAI PENDIDIKAN DALAM SURAT LUQMAN - Mukodi Mukodi (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2011)
The result of this study —library research— showed that the values of Islamic education are contained in the Holy Qur’an surah Luqman verses 12-19. There are at least three basic education, namely aqidah education, syari’ah education and character education. Aqidah education, there are two things: (1) prohibition of associating partners with Allah. Luqman al-Hakim himself had to prioritize monotheism education (tauhid) to his children, (2) believe in the place of hereafter. Luqman ordered his children to believe the reward of all his deeds. Especially retaliation for our gratitude to Him for every blessing and our sense of respect for both parents. Syari’ah Education, there are two things, namely a command set up prayer and amar ma‘rūf nahy munkar. Character education, which is the command to ingratitude towards Allah SWT. For all the blessings and grace of God, we should be grateful to Him.